2022
DOI: 10.3389/fpubh.2022.857284
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of Fifteen Years Suicide Trends Using Population-Level Data From Croatian Committed Suicides Registry

Abstract: ObjectivesThe provide a descriptive analysis of the available population-level aggregated data on committed suicides in the Republic of Croatia, in the 2004–2018 period, showing emerging trends in suicide incidence focusing on sex/age/geographical distribution of suicides and the primary and secondary causes of suicide mortality, as well as making comparisons with similar neighboring neighboring countries.MethodsThe aggregated suicide data were obtained from the Croatian Committed Suicides Registry, a national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…The present study observed no regular patterns of suicide; nevertheless, previous studies reported the highest suicide frequency in the spring, early summer and fall (61,97,98). Certain researchers have also confirmed the relationship between season and suicide in young age groups (99,100).…”
Section: Discussioncontrasting
confidence: 87%
“…The present study observed no regular patterns of suicide; nevertheless, previous studies reported the highest suicide frequency in the spring, early summer and fall (61,97,98). Certain researchers have also confirmed the relationship between season and suicide in young age groups (99,100).…”
Section: Discussioncontrasting
confidence: 87%